1995
DOI: 10.1161/01.res.77.4.803
|View full text |Cite
|
Sign up to set email alerts
|

cGMP-Dependent Protein Kinase Regulation of the L-Type Ca 2+ Current in Rat Ventricular Myocytes

Abstract: Regulation of L-type Ca2+ channel current [ICa(L)] by cGMP-dependent protein kinase (PK-G) was investigated in ventricular myocytes from 2- to 21-day-old rats using whole-cell voltage clamp with internal perfusion. ICa(L) was elicited by a depolarizing pulse to +10 mV from a holding potential of -40 mV. Stimulated ICa(L) (by 2 mumol/L isoproterenol) was inhibited to the basal level by internal perfusion with 50 nmol/L PK-G (activated by 8Br-cGMP, 0.1 mumol/L). When ICa(L) was enhanced by Bay K8644 (1 mumol/L),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
1
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 30 publications
10
80
1
2
Order By: Relevance
“…This partial (Ͻ 50%) inhibition is selective, i.e., cGMP and NO inhibit only I Ca,L (T-type Ca 2ϩ current is not targeted). The regulation by cGMP resembles that described in rabbit pulmonary artery and in portal vein and rat ventricular cells (4,(49)(50)(51)(52). Our results suggest that the effect of NO on Ca 2ϩ -channel currents of human coronary myocytes is mediated through a rise in intracellular cGMP.…”
Section: Discussionsupporting
confidence: 81%
“…This partial (Ͻ 50%) inhibition is selective, i.e., cGMP and NO inhibit only I Ca,L (T-type Ca 2ϩ current is not targeted). The regulation by cGMP resembles that described in rabbit pulmonary artery and in portal vein and rat ventricular cells (4,(49)(50)(51)(52). Our results suggest that the effect of NO on Ca 2ϩ -channel currents of human coronary myocytes is mediated through a rise in intracellular cGMP.…”
Section: Discussionsupporting
confidence: 81%
“…Secondly, we have demonstrated that the stimulation of myocyte guanylyl cyclase and the increase in intracellular cGMP by muscarinic cholinergic agonists are dependent on the activation of myocyte eNOS. Although the effects of increased intracellular cGMP on I Ca-L in myocytes have been reported to range from stimulatory to neutral to inhibitory, depending on the specific species, myocyte phenotype, and level of intracellular cAMP, the data reported here support a growing consensus that cGMP suppresses the magnitude of Ca 2ϩ influx via I Ca-L in cells that have elevated cAMP levels (19,(29)(30)(31)(32). A similar NO͞cGMP-dependent signal transduction pathway also has been demonstrated in cardiac pacemaker cells (33,34) and basophilic cells (35) after exposure to adenosine.…”
Section: Discussionmentioning
confidence: 50%
“…27 In agreement with these findings, 8-BrcGMP has been shown to inhibit I Ca,L in ferret right ventricular myocytes, 28 and the cGMP dependent protein kinase (PKG) has been reported to cause a 40% inhibition of I Ca,L in rat ventricular myocytes. 29 Indeed, we found increased cGMP levels in the nNOS overexpressing myocytes. From the inhibitory effect of nNOS on L-type Ca 2ϩ -channel currents, one would predict an attenuation of the ␤-AR response when nNOS activity is increased.…”
Section: Nnos and Inotropic Reservementioning
confidence: 61%